2011
DOI: 10.1186/1475-2891-10-106
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of eating patterns and overweight - a follow-up study of Norwegian schoolchildren from middle childhood to early adolescence

Abstract: BackgroundThe aim of this study was to describe eating patterns in early adolescence and to determine associations between eating patterns and overweight from middle childhood (4th grade, 9 to 10 years old) to early adolescence (7th grade, 12 to 13 years old).MethodsChildren were recruited from primary schools in Telemark County, Norway. Dietary data were obtained by parental report using a food frequency questionnaire. Height and weight were objectively measured, and overweight was defined using international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(120 citation statements)
references
References 48 publications
11
107
0
Order By: Relevance
“…"Dieting" DP had greater adherence among girls and wealthier subjects. Consistently, a study carried out by Oellingrath et al [31] with Norwegian pre-teens and adolescents identified four DPs using PCA (snacks, convenient, varied Norwegian, and dieting), reporting greater adherence to "Dieting" DP among girls. Additionally, in a study including Portuguese adolescents aged 13 years, 40% of them adhered to a dietary pattern named "low intake", which was associated with higher proportion of overweight/obese [13].…”
Section: Discussionmentioning
confidence: 60%
“…"Dieting" DP had greater adherence among girls and wealthier subjects. Consistently, a study carried out by Oellingrath et al [31] with Norwegian pre-teens and adolescents identified four DPs using PCA (snacks, convenient, varied Norwegian, and dieting), reporting greater adherence to "Dieting" DP among girls. Additionally, in a study including Portuguese adolescents aged 13 years, 40% of them adhered to a dietary pattern named "low intake", which was associated with higher proportion of overweight/obese [13].…”
Section: Discussionmentioning
confidence: 60%
“…Not surprisingly, overweight in 4th grade appeared to be the most important predictor of overweight in 7th grade. We have previously reported a high degree of BMI tracking from 4th to 7th grade in the same cohort (18) . However, adjusting for physical activity had a larger impact than overweight at 4th grade on the estimated odds ratios for meal skipping.…”
Section: Discussionmentioning
confidence: 63%
“…The detailed methods for the 4th grade data collection have been described previously (17) . An identical procedure was used for data collection in the 7th grade (18) . In brief, all primary schools in Telemark County were invited to participate in the study at both time points.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…We have previously related overweight to a low intake of the varied Norwegian eating pattern (31) . To investigate independent relationships, BMI was considered an important confounder and adjusted for in the present analyses.…”
Section: Discussionmentioning
confidence: 99%